Cigarette Smoking, Smoking Cessation, and Long-Term Risk of 3 Major Atherosclerotic Diseases - Ding, Ning; Sang, Yingying; Chen, Jingsha; Ballew, Shoshana H; Kalbaugh, Corey A; Salameh, Maya J; Blaha, Michael J; Allison, Matthew; Heiss, Gerardo; Selvin, Elizabeth; Coresh, Josef; Matsushita, Kunihiro (Journal of the American College of Cardiology, 2019)
Public statements about the effect of smoking on cardiovascular disease are predominantly based on investigations of coronary heart disease (CHD) and stroke, although smoking is recognized as a strong risk factor for peripheral artery disease (PAD). No study has comprehensively compared the long-term association of cigarette smoking and its cessation with the incidence of 3 major atherosclerotic diseases (PAD, CHD, and stroke). The aim of this study was to quantify the long-term association of cigarette smoking and its cessation with the incidence of the 3 outcomes. A total of 13,355 participants aged 45 to 64 years in the ARIC (Atherosclerosis Risk In Communities) study without PAD, CHD, or stroke at baseline (1987 to 1989) were included. The associations of smoking parameters (pack-years, duration, intensity, and cessation) with incident PAD were quantified and contrasted with CHD and stroke using Cox models. Over a median follow-up of 26 years, there were 492 PAD cases, 1,798 CHD cases, and 1,106 stroke cases. A dose-response relationship was identified between pack-years of smoking and 3 outcomes, with the strongest results for PAD. The pattern was consistent when investigating duration and intensity separately. A longer period of smoking cessation was consistently related to lower risk of PAD, CHD, and stroke, but a significantly elevated risk persisted up to 30 years following smoking cessation for PAD and up to 20 years for CHD. All smoking measures showed significant associations with 3 major atherosclerotic diseases, with the strongest effect size for incident PAD. The risk due to smoking lasted up to 30 years for PAD and 20 years for CHD. Our results further highlight the importance of smoking prevention and early smoking cessation, and indicate the need for public statements to take PAD into account when acknowledging the impact of smoking on overall cardiovascular health.